Pengaruh Financial Literacy dan Sosiodemografi terhadap Keputusan Investasi Individu dengan Bias Perilaku Sebagai Variabel Intervening - Prayogi Prayogi; Fitriaty Fitriaty; Musnaini Musnaini (Universitas Batanghari Jambi, 2023)
This study entitled the effect of financial literacy and sociodemography on individual investment decisions with behavioral bias as an intervening variable. The purpose of this study was to analyze the direct and indirect effects of financial literacy and sociodemography on investment decisions through behavioral bias. The research method used is a quantitative descriptive analysis method with the Structural Equation Modeling (SEM-PLS) model using SmartPLS. Based on the results of the study, it shows that financial literacy has no significant effect on the individual investment decisions of Jambi High Court employees. Sociodemography has a significant effect on the individual investment decisions of Jambi High Court employees. Financial literacy has no significant effect on individual behavioral biases of Jambi High Court employees. Sociodemography has no significant effect on individual behavioral biases at the Jambi High Court. Behavioral bias has a significant effect on the individual investment decisions of Jambi High Court employees. Financial literacy does not have a significant effect on investment decisions through behavioral bias. Sociodemographics have a significant influence on investment decisions through behavioral biases.